2004
DOI: 10.1128/iai.72.5.2742-2752.2004
|View full text |Cite
|
Sign up to set email alerts
|

Engulfment ofNeisseria gonorrhoeae: Revealing Distinct Processes of Bacterial Entry by Individual Carcinoembryonic Antigen-Related Cellular Adhesion Molecule Family Receptors

Abstract: Individual Neisseria gonorrhoeae colony opacity-associated (Opa) protein variants can bind up to four different carcinoembryonic antigen-related cellular adhesion molecule (CEACAM) receptors. Most human cells encountered by gonococci express a combination of CEACAM receptors, thereby complicating the elucidation of intracellular signaling pathways triggered by individual receptors. Here, we compare the process of bacterial engulfment by a panel of stably transfected HeLa epithelial cell lines expressing each C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 44 publications
6
84
0
Order By: Relevance
“…3B). In contrast, gentamicin assaybased viable counts of gonococci internalized via CEA-CAM3 decline rapidly, consistent with previous reports (McCaw et al, 2004). These results further stress the limitations of antibiotic protection assays, where the read-out (recovered viable bacteria) is influenced by both the efficiency of uptake as well as rate of intracellular killing or multiplication of the bacteria.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…3B). In contrast, gentamicin assaybased viable counts of gonococci internalized via CEA-CAM3 decline rapidly, consistent with previous reports (McCaw et al, 2004). These results further stress the limitations of antibiotic protection assays, where the read-out (recovered viable bacteria) is influenced by both the efficiency of uptake as well as rate of intracellular killing or multiplication of the bacteria.…”
Section: Discussionsupporting
confidence: 73%
“…3A). These results demonstrated that bacteria taken up via CEACAM3 are rapidly killed inside human epithelial cells and similar observations have been reported by others (McCaw et al, 2004;Schmitter et al, 2004). Importantly, when the flow cytometric analysis was performed on samples infected and gentamicin treated identical to the ones used in the antibiotic protection assay, the fluorescence signal obtained 30, 60 and 120 min after gentamicin addition did not decrease (Fig.…”
Section: Pharmacological Blockage Of Internalization Can Be Evaluatedsupporting
confidence: 71%
See 1 more Smart Citation
“…6). CEACAMs mediate binding to and engulfment of Neisseria gonorrhoeae [12] and E. coli [35] by epithelial cells. We show that huMC express CEACAM1 and may be involved in internalization and engulfment of E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules included the ␤1 integrins and the newly characterized family of CEACAM molecules. CEACAM1, a receptor known to bind bacteria in other cell types [12], was up-regulated threefold at Fig. 4.…”
Section: Coincubation With E Coli Up-regulates Expression Of Adhesiomentioning
confidence: 99%